2008
DOI: 10.1007/s10238-008-0020-2
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood dendritic cells prevent the differentiation of naïve T-helper cells towards Th1 irrespective of their subtype

Abstract: Allogeneic cord blood transplantation is associated with a less severe graft-versus-host disease (GVHD). This observation is thought to be due to immaturity of cord blood cell immune capabilities. Dendritic cells (DCs) are the most potent antigen-presenting cells of the immune system capable of initiation and regulation of immune responses. In this investigation, we hypothesized that nonmanipulated cord blood dendritic cells (CBDCs) not only differ in their functional maturity from adult peripheral blood DCs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
2
18
1
Order By: Relevance
“…Another interesting result is that T. cruzi-activated cord blood eDCs favored the production of IFN-c over IL-13, whereas in the absence of parasites, cord blood eDCs displayed a type 2 response releasing higher levels of IL-13, as previously described [21,22]. We can reasonably hypothesize that CD8 ?…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Another interesting result is that T. cruzi-activated cord blood eDCs favored the production of IFN-c over IL-13, whereas in the absence of parasites, cord blood eDCs displayed a type 2 response releasing higher levels of IL-13, as previously described [21,22]. We can reasonably hypothesize that CD8 ?…”
Section: Discussionsupporting
confidence: 50%
“…Neonatal DCs display defective expression of co-stimulatory molecules [10,[12][13][14][15][16] and a deficient production of the type 1 polarizing cytokines interleukin (IL)-12 and IFN-b [17,18]. They are less effective than adult DCs in stimulating T cell proliferation [19,20] and induce a poor Th1 response [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, if umbilical cord blood is transplanted, the DCs are immature and Th1 responses may be curtailed. 34 Thus, the relative importance of each pathway must be determined empirically for newer donor cell populations such as embryonic stem cell-derived HSCs or stem cells which do not give rise to APCs.…”
Section: Discussionmentioning
confidence: 99%
“…The final published version may differ from this proof. 11 11 the UCB-derived monocytes was lower than that of APB-derived monocytes (Fig. 1B).…”
Section: Ucb-derived Monocytes Successfully Differentiate Into Immatumentioning
confidence: 57%
“…However, its application is now limited to only children since the absolute number of hematopoietic stem cells in a unit of UCB is too low to be applied to adults [9]. Previous studies have demonstrated that UCB-DCs display a low level of co-stimulatory molecules, low responsiveness to microbial components, and low lymphocyte-activating capacities [10,11]. These tolerogenic properties of UCB-DCs lead to alleviation of immune rejection after the transplantation [12].…”
Section: Introductionmentioning
confidence: 95%